การควบคุมหุ่นยนต์แขนกลโดยใช้วิธีการควบคุมความเร็วสัญญาณพัลส์: The control of a robot arm using speed pulse control method - Poorahong, Tharathip; Prainetr, Supachai (Asian Health, Science and Technology Reports, 2010)
This paper research a present a control of a robot arm using by variable speed pulse control method(PLSV). TheServo amplifier controls the movement quantity and the speed according to the command given by the positioning controller. The servo motor then transmits rotation to the drive mechanism after receiving signals from the servo amplifier. Result the experiment the control a robot arm using by variable speed pulse control method(PLSV) can reduce the position errors and frequent operation is enabled by a low inertial motor, the maximum torque is increased and the system can be applied to a wide variety of machines.